COMPARISON OF THE STABILITY OF THE BOAT WITH AND WITHOUT THE USE OF CADIK - Syafriadi '; Jonny Zain; Ronald M Hutauruk (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted on 24 April to 7 May 2013, which took place in the village of Lohong. The purpose of this study was to assess the stability of the boat with and without the use of cadik over the stability curve Hidromax software. The method used in this study is asurvey method. Boat primary measure obtained is 8 m LOA, LPP 6 m, 7 m LWL, loaded 0.6 m,0.8 m high and 1 m wide boat. results of the analysis indicate that the boat using cadik rate stability is better than that not using cadik boats, where the maximum heigh tis 0,429 GZ cadik boats rad m-high and boats without cadik GZ is 0.262 m-rad, the difference is caused by the addition of cadik because the cadik on the boat could improve the stability of the boat and if the boat motion, cadik also reserve buoyancy for the boatKeywords: stability of the boat, cadik, software Hidromax